Description of a new species of spider wasp Genus Machaerothrix Haupt(Hymenoptera: Pompilidae) from India with reports on its host ssociation and nesting behaviour - Binoy, C.; Anju, K.; Thejass, P. (Zootaxa, 2020)
The little-known spider wasp genus Machaerothrix Haupt, 1938 is recorded for the first time from India with the description and illustrations of both sexes of a seventh species from the World. The biology, habitat, prey preference and transport, nest structure and nesting behaviour of the new species is studied and the association of the wasps with salticid spiders (Araneae: Salticidae) is here validated.